Real-time rendering - Akenine-Moller, Tomas; Haines, Eric;Hoffman, Naty;Pesce, Angelo;Iwanicki, Michal;Hillaire, Sebastien (Boca Raton, Florida : CRC Press, 2018)
Thoroughly updates, this fourth edition of Real-Time rendering focuses on modern techniques used to generate synthetic three-dimensional imagesin a fraction of a second. It provides a guide to the many algorithms that have been developed and applied over the past decade, and includes over 1100 new references.
1. Introduction -- 2. The Graphics rendering pipeline -- 3. The Graphics processing unit -- 4. Transforms -- 5. Shading basics -- 6. Texturing -- 7. Shadows -- 8. Light and color -- 9. Physically based shading -- 10. Local illumination -- 11. Global illumination -- 12. Image-space effects -- 13. Beyond polygons -- 14. Volumetric and translucency rendering -- 15. Non-photorealistic rendering -- 16. Polygonal techniques -- 17. Curvfes and curved surfaces -- 18. Pipeline optimization -- 19. Acceleration algorithms -- 20. Efficient shading -- 21. Virtual and augmented reality -- 22. Intersection test methods -- 23. Graphics hardware -- 24. The Future
Includes bibliographical references and index.
Keywords: COMPUTER GRAPHICS